Forgiveness is not a musical instrument - Waltham-Smith, N (Editura Universitatii Petrol-Gaze din Ploiesti, 2024)
Derrida’s Le Parjure et le Pardon is heard as an offstage voice to the global mediatization of proceedings concerning genocide in the International Court of Justice in late 2023 and early 2024. Focusing on the Sixth Session of the first year, which remained unpublished until 2019 (2022 in English), the article follows Derrida is questioning whether a shared hearing or attunement is required for forgiveness and reconciliation. Far from absolving states from responsibility, Derrida’s insistence that any forgiveness and reconciliation worthy of the name exceed identificatory concord or reciprocity puts pressure on those with the most power to decide for peace before any accord to come.